2015
DOI: 10.1038/cr.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

High salt primes a specific activation state of macrophages, M(Na)

Abstract: High salt is positively associated with the risk of many diseases. However, little is known about the mechanisms. Here we showed that high salt increased proinflammatory molecules, while decreased anti-inflammatory and proendocytic molecules in both human and mouse macrophages. High salt also potentiated lipopolysaccharide-induced macrophage activation and suppressed interleukin 4-induced macrophage activation. High salt induced the proinflammatory aspects by activating p38/cFos and/or Erk1/2/cFos pathways, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
176
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(199 citation statements)
references
References 48 publications
8
176
4
4
Order By: Relevance
“…Zhang et al described a specific activation state of macrophages induced by high salt, which they termed M(Na). This state is characterized by enhanced expression of proinflammatory genes and suppressed expression of antiinflammatory genes (25). Kirabo et al demonstrated that dendritic cells activate T cells in hypertension through presentation of isoketal-modified peptides (26).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al described a specific activation state of macrophages induced by high salt, which they termed M(Na). This state is characterized by enhanced expression of proinflammatory genes and suppressed expression of antiinflammatory genes (25). Kirabo et al demonstrated that dendritic cells activate T cells in hypertension through presentation of isoketal-modified peptides (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that these high sodium concentrations can alter immune cell function. Exposure of either mouse macrophages or T cells to high NaCl concentration drives them toward a pro-inflammatory state Jantsch et al, 2015;Jörg et al, 2016;Kleinewietfeld et al, 2013;Wu et al, 2013;Zhang et al, 2015). Specifically, elevation of extracellular NaCl promotes production of IL-17A by T cells and salt feeding exacerbates experimental allergic encephalitis, a disease driven by this cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…We show upregulation in patients, which is in line with the exciting novel views linking adaptive immunity with hyperosmolarity. 8,9 MATERIALS AND METHODS Patients and Cell Lines Patient material was collected at the University Hospitals of Ghent, Antwerp, Barcelona and Aachen. Frozen diagnostic limb muscle biopsies were obtained after informed patient and/or parent consent, and the methodologies used were reviewed and approved by the hospitals' Local Ethics Committees.…”
mentioning
confidence: 99%